A MOF mixed matrix membrane for natural gas purification and preparation method thereof

By using a mixed matrix membrane of Hoffmann-type MOF (CoNi-DABCO) filler with small pore size and high density unsaturated metal sites in natural gas purification, the problems of insufficient gas permeability and blockage of filler channels in the prior art are solved, and efficient CH4/N2 separation performance is achieved.

CN118949722BActive Publication Date: 2025-03-18BEIJING UNIV OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411344062.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-03-18
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

In the prior art, in the process of CH4/N2 separation in natural gas, there are problems such as insufficient gas permeability flux and the filler channel being easily blocked by flexible molecular chains, resulting in poor separation performance.

Method used

Hoffmann-type MOF (CoNi-DABCO) with small pore size and high density unsaturated metal sites was used as filler, combined with rubber polymer PDMS, and the MOF mixed matrix membrane was prepared to improve gas permeability and optimize CH4/N2 selectivity.

Benefits of technology

The CH4 permeability flux of PDMS membrane was significantly improved to reach 1285Barrer, and good CH4/N2 selectivity was maintained, which was better than the separation performance of most polymer films, MOF films and MMMs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949722B_ABST
    Figure CN118949722B_ABST
Patent Text Reader

Abstract

The present invention provides a MOF mixed matrix membrane for natural gas purification and a preparation method thereof. The MOF mixed matrix membrane for natural gas purification is prepared by the preparation method; the preparation method comprises: dissolving a nickel source and a cobalt salt in deionized water, ultrasonically treating, and obtaining a suspension; dissolving 1,4-diazooctane in a methanol / water mixed solvent, adding the mixture to the suspension, stirring, centrifuging, washing, and drying in sequence to obtain CoNi-DABCO nanoparticles; adding the CoNi-DABCO nanoparticles to n-heptane, stirring and ultrasonically obtaining a dispersion; adding PDMS to the dispersion, stirring, adding a crosslinking agent and a catalyst, and mixing uniformly to obtain a casting liquid; fixing a PVDF substrate, casting the casting liquid on the substrate, and drying after the solvent evaporates. The present invention uses PDMS as a polymer matrix, selects a Hofmann-type MOF with a microporous structure and a high-density unsaturated metal site as a filler, and the prepared MMMs show excellent separation performance, CH4 permeation flux is increased by 2 times, and CH4 / N2 selectivity can reach 3.7.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas separation membranes, and in particular relates to a MOF mixed matrix membrane for natural gas purification and a preparation method thereof. Background Art

[0002] Natural gas (mainly CH4) is a basic high-quality, efficient and clean fossil energy, and has a wide range of application needs in industrial and civilian fields. However, natural gas reservoirs are often contaminated by nitrogen (N2). Therefore, it is necessary to develop efficient separation technology to achieve CH4 / N2 separation. Due to the similar kinetic diameters and polarizabilities of the two, the separation of CH4 and N2 is considered to be a very challenging process. The industry mainly uses energy-intensive low-temperature distillation methods to achieve the separation of the two, which has high energy consumption and cost. Membrane separation technology is considered to be a separation technology with great prospects because of its high separation efficiency, simple operation, energy saving and environmental protection.

[0003] Mixed-matrix membranes (MMMs) can combine the excellent mechanical properties and processability of polymers with the advantages of fillers in gas sieving or gas transmission, and have great application prospects. For MMMs, the properties of the polymer as the continuous phase will play a decisive role in the separation performance of MMMs, which determines the lower limit of the separation performance. Metal-organic frameworks (MOFs) have high specific surface area, porosity, regular and adjustable pore structure and chemical diversity. MMMs based on MOF materials have been widely used in gas separation.

[0004] Compared with common glassy polymers such as polysulfone and polyimide, which have lower CH4 / N2 selectivity and gas permeation flux, rubbery polymer polydimethylsiloxane (PDMS) has excellent CH4 / N2 selectivity and is a suitable candidate for the preparation of MMMs. Gas permeation flux and selectivity are two important parameters for measuring membrane separation performance. While maintaining good selectivity, high gas permeation flux can save investment costs and energy consumption. Therefore, while ensuring good CH4 / N2 selectivity of PDMS membrane, it is necessary to add porous fillers to the PDMS membrane to further improve its CH4 permeation flux. In addition, although the flexible PDMS molecular chain can ensure the interface compatibility with the filler, when the pore size of the porous filler is larger than the size of the PDMS molecular chain, it will cause the filler pores to be blocked, hindering the performance of the filler properties, and is not conducive to improving the separation performance of MMMs. Therefore, the rational selection of porous fillers is a key factor in achieving the above goals.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a MOF mixed matrix membrane for natural gas purification and a preparation method thereof to solve the above problems.

[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0008] The present invention first provides a method for preparing a MOF mixed matrix membrane for natural gas purification, the preparation method comprising the following steps:

[0009] S1: dissolving a nickel source and a cobalt salt in deionized water, and then performing ultrasonic treatment to obtain a suspension; dissolving 1,4-diazaoctane in a methanol / water mixed solvent, adding the mixture to the suspension, stirring at a certain temperature, centrifuging, washing and drying in sequence to obtain CoNi-DABCO nanoparticles; the nickel source comprises potassium tetracyanonickelate hydrate; the cobalt salt comprises cobalt nitrate hexahydrate; the ultrasonic treatment takes 0.5-1.0 h; the molar ratio of the nickel source, the cobalt salt and 1,4-diazaoctane is 1:1:1; the volume ratio of water and methanol in the mixed solvent is 1:1; the stirring temperature is 40-45°C, and the time is 3-4 h; the drying comprises drying in a vacuum oven at 120-150°C for 10-15 h;

[0010] S2: adding the CoNi-DABCO nanoparticles obtained in S1 to n-heptane, stirring and ultrasonicating to obtain a dispersion; the mass ratio of the CoNi-DABCO nanoparticles to the n-heptane is 1:5-15;

[0011] S3: adding PDMS to the dispersion in S2, stirring, then adding a crosslinking agent and a catalyst, mixing evenly to obtain a casting solution; the mass ratio of the added PDMS to the CoNi-DABCO nanoparticles is 1:2-10; the crosslinking agent includes tetraethyl orthosilicate; and the catalyst includes dibutyltin dilaurate;

[0012] S4: Fix the PVDF substrate on a glass plate, cast the casting solution obtained in S4 on the PVDF substrate using a doctor blade, and after the solvent evaporates, dry it at 80-100° C. to obtain the MOF mixed matrix membrane for natural gas purification. The PVDF substrate is pretreated with ethanol and deionized water before fixing;

[0013] Preferably, the PDMS is added to the dispersion in batches;

[0014] The batch adding includes: adding PDMS of different mass ratios in batches and sequentially until 100 wt.% of PDMS is added.

[0015] Further preferably, the adding in batches further comprises adding 5-10wt.%, 15-25wt.%, 25-35wt.% and 30-45wt.% of PDMS in sequence, and the total amount added is 100wt.%.

[0016] More preferably, each time the PDMS with different mass ratios is added in sequence, stirring is performed, and the total stirring time is 1-2 hours.

[0017] The invention also provides a mixed matrix membrane, which is prepared by the preparation method.

[0018] The gas permeation flux of the existing PDMS membrane needs to be further improved, and when PDMS is used as the polymer matrix, the filler pores are easily blocked by flexible molecular chains. The present invention selects MOF with a smaller pore size and a high-density unsaturated metal site as the filler. Thanks to the small pore size of MOF, the pore blockage phenomenon is alleviated to a great extent, which helps the gas molecules to diffuse into the MOF material. The preferential adsorption of CH4 by the high-density unsaturated metal sites promotes the transmission of CH4 in the mixed matrix membrane. The above two aspects jointly achieve a significant improvement in the gas permeation flux of the PDMS membrane.

[0019] Beneficial effects of the present invention:

[0020] Compared with the low-temperature distillation method used in industry to separate CH4 / N2, the membrane separation method has the advantages of low energy consumption, high separation efficiency, simple operation, etc.; and because PDMS, one of the raw materials of the present invention, is a rubbery polymer, the flexible molecular chain ensures the interface compatibility with the CoNi-DABCO nanoparticles, so that the MMMs maintain good CH4 / N2 selectivity; at the same time, CoNi-DABCO has a smaller pore size, which slows down the pore clogging phenomenon, and preferentially adsorbs CH4 molecules, which promotes the transmission of CH4 molecules in the membrane and improves the CH4 permeation flux of the PDMS membrane.

[0021] In order to achieve effective separation of CH4 and N2 in natural gas, the present invention uses PDMS with good CH4 / N2 selectivity as the polymer matrix, selects Hofmann-type MOF (CoNi-DABCO) with microporous structure and high-density unsaturated metal sites as filler, and prepares a series of MMMs. Compared with PDMS, when the CoNi-DABCO loading is 20wt.%, the CH4 permeation flux of MMMs is increased by 2 times to 1285 Barrer and has good CH4 / N2 selectivity of up to 3.7, which is better than the separation performance of most polymer membranes, MOF membranes and MMMs reported so far. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 is a scanning electron microscope image of the CoNi-DABCO nanoparticles prepared in Example 1;

[0024] Figure 2 is the adsorption-desorption isotherm of CO2 of the CoNi-DABCO nanoparticles prepared in Example 1 at 195K;

[0025] Figure 3 is a pore size distribution diagram of the CoNi-DABCO nanoparticles prepared in Example 1;

[0026] Figure 4 The CH4 and N2 adsorption-desorption isotherms of CoNi-DABCO prepared in Example 1 at 298K;

[0027] Figure 5 X-ray diffraction patterns of the mixed matrix films provided for CoNi-DABCO nanoparticles, Examples 1-4, and Comparative Example 1;

[0028] Figure 6 Scanning electron microscope cross-sectional images of the CoNi-DABCO nanoparticles provided in the present application at a magnification of 6000 times and of the MMMs provided in Comparative Example 1 and Examples 1-4 at a magnification of 1000 times;

[0029] Figure 7 Scanning electron microscope cross-sectional images of the CoNi-DABCO nanoparticles provided in the present application at a magnification of 6000 times and of the MMMs provided in Comparative Example 1 and Examples 1-4 at a magnification of 5000 times;

[0030] Figure 8 Scanning electron microscope surface images of the CoNi-DABCO nanoparticles provided in the present application at a magnification of 6000 times and of the MMMs provided in Comparative Example 1 and Examples 1-4 at a magnification of 3000 times;

[0031] Fig. 9 A comparison diagram of the experimental adsorption isotherm and the theoretical adsorption isotherm of CH4 at 298K for MMMs provided in Example 2;

[0032] Fig.10Adsorption isotherms of CH4 and N2 for MMMs provided in Example 2 and Comparative Example 1 at 298K;

[0033] Fig.11 A comparison chart of CH4 / N2 separation performance between the MMMs provided in Example 2 and previously reported separation membranes;

[0034] Fig.12 This is a structural diagram of ZIF-71 provided in Comparative Example 2 and CoNi-DABCO provided in Example 2. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] The mixed matrix membrane is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0038] S1. Potassium tetracyanonic acid hydrate (1.205 g, 5 mmol) and cobalt nitrate hexahydrate (1.455 g, 5 mmol) were dissolved in 20 mL of deionized water, and ultrasonically treated for 1 h to obtain a suspension; 1,4-diazaoctane (0.561 g, 5 mmol) was dissolved in a mixed solvent consisting of 50 mL of deionized water and 50 mL of methanol, and then added to the above suspension. The resulting mixture was stirred at 40° C. for 3 hours, and the product was collected by centrifugation, washed several times with methanol, and then dried in a vacuum oven at 150° C. for 12 hours to obtain nanoparticles, which were recorded as CoNi-DABCO;

[0039] S2, taking 0.2 g of the CoNi-DABCO nanoparticles obtained in S1 and adding them into 3.2 g of n-heptane, stirring and ultrasonicating them to make them dispersed evenly to obtain a dispersion;

[0040] S3, taking a total of 1.8g of PDMS and adding it to the dispersion obtained in S2, first adding 10wt.% of PDMS, stirring for 1-2h, then adding 20wt.%, 30wt.% and 40wt.% of PDMS in sequence, stirring evenly, volatilizing and removing 0.2g of n-heptane under stirring, then adding crosslinking agent ethyl orthosilicate and catalyst dibutyltin dilaurate, mixing evenly to obtain a casting solution;

[0041] S4. Fix the PVDF substrate pretreated with ethanol and deionized water on a glass plate with tape, cast the casting liquid on the PVDF substrate with a doctor blade, slowly evaporate the solvent at room temperature, remove the membrane and transfer it to an oven at 80°C for drying to obtain the product, which is the mixed matrix membrane MMMs.

[0042] It was calculated that the loading amount of MOF material (ie CoNi-DABCO) in the MMMs obtained in this example was 10 wt.%.

[0043] The scanning electron microscope image of the CoNi-DABCO nanoparticles prepared in this example is as follows: Figure 1 As shown by Figure 1 It can be seen that the CoNi-DABCO nanoparticles synthesized in the present invention have uniform shapes and particle sizes of about 100 nm. Small-sized nanoparticles are conducive to uniform dispersion of fillers and stronger polymer-filler interactions.

[0044] The adsorption-desorption isotherms of the CoNi-DABCO nanoparticles prepared in this example for CO2 at 195K are as follows: Figure 2 As shown in Figure 2, at 195K, CO2 was used as the probe molecule and the BET specific surface area of ​​CoNi-DABCO was 349 m 2 g -1 ,Depend on Figure 2 It can be seen that it exhibits a type I adsorption isotherm, which is a characteristic of microporous materials.

[0045] The pore size distribution of the CoNi-DABCO nanoparticles prepared in this example is as follows: Figure 3 As shown by Figure 3 It can be seen that the pore size of CoNi-DABCO nanoparticles is concentrated in It is a microporous material.

[0046] Figure 4 The CH4 and N2 adsorption-desorption isotherms of CoNi-DABCO prepared in Example 1 at 298K are shown in Table 1. Figure 4 It can be seen that the adsorption capacity of CoNi-DABCO prepared in this example for CH4 is 25.7 cm 3 g -1 The adsorption capacity of N2 is 2.95 cm 3 g -1 ,The results show that CoNi-DABCO preferentially adsorbs CH4 molecules, which helps to improve the CH4 / N2 separation performance of MMMs.

[0047] Since CoNi-DABCO absorbs n-heptane, which increases the viscosity of the dispersion and is not conducive to uniform dispersion of the nanoparticles, the present invention adds additional n-heptane solvent and then removes it by stirring and volatilization to ensure that the concentration of PDMS remains unchanged.

[0048] Example 2

[0049] The mixed matrix membrane is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0050] S1. Potassium tetracyanonic acid hydrate (1.205 g, 5 mmol) and cobalt nitrate hexahydrate (1.455 g, 5 mmol) were dissolved in 20 mL of deionized water, and ultrasonically treated for 1 h to obtain a suspension; 1,4-diazaoctane (0.561 g, 5 mmol) was dissolved in a mixed solvent consisting of 50 mL of deionized water and 50 mL of methanol, and then added to the above suspension. The resulting mixture was stirred at 40° C. for 3 hours, and the product was collected by centrifugation, washed several times with methanol, and then dried in a vacuum oven at 150° C. for 12 hours to obtain nanoparticles, which were recorded as CoNi-DABCO;

[0051] S2, taking 0.4 g of the CoNi-DABCO nanoparticles obtained in S1 and adding them into 3.4 g of n-heptane, stirring and ultrasonicating them to make them dispersed evenly to obtain a dispersion;

[0052] S3, taking a total of 1.6g of PDMS and adding it to the dispersion obtained in S2, first adding 10wt.% of PDMS, stirring for 1-2h, then adding 20wt.%, 30wt.% and 40wt.% of PDMS in sequence, stirring evenly, volatilizing and removing 0.4g of n-heptane under stirring, then adding crosslinking agent ethyl orthosilicate and catalyst dibutyltin dilaurate, mixing evenly to obtain a casting solution;

[0053] S4. Fix the PVDF substrate pretreated with ethanol and deionized water on a glass plate with tape, cast the casting liquid on the PVDF substrate with a doctor blade, slowly evaporate the solvent at room temperature, remove the membrane and transfer it to an oven at 80°C for drying to obtain the product, which is the mixed matrix membrane MMMs.

[0054] It was calculated that the loading amount of MOF material (ie CoNi-DABCO) in the MMMs obtained in this example was 20 wt.%.

[0055] Example 3

[0056] The difference from Example 1 is that the CoNi-DABCO nanoparticles used in S2 are 0.5 g and n-heptane is 3.6 g;

[0057] S3: A total of 1.5 g of PDMS is added to the dispersion obtained in S2, first 10 wt.% of PDMS is added, and after stirring, 20 wt.%, 30 wt.% and 40 wt.% of PDMS are added in sequence, and after stirring evenly, 0.6 g of n-heptane is evaporated and removed under stirring, and then crosslinking agent ethyl orthosilicate and catalyst dibutyltin dilaurate are added, and mixed evenly to obtain a casting solution;

[0058] It was calculated that the loading amount of MOF material (ie CoNi-DABCO) in the MMMs obtained in this example was 25 wt.%.

[0059] Example 4

[0060] The difference from Example 1 is that the CoNi-DABCO nanoparticles used in S2 are 0.6 g and n-heptane is 3.8 g;

[0061] S3: A total of 1.4 g of PDMS is added to the dispersion obtained in S2, first 10 wt.% of PDMS is added, and after stirring, 20 wt.%, 30 wt.% and 40 wt.% of PDMS are added in sequence, and after stirring evenly, 0.8 g of n-heptane is evaporated and removed under stirring, and then crosslinking agent ethyl orthosilicate and catalyst dibutyltin dilaurate are added, and mixed evenly to obtain a casting solution;

[0062] It was calculated that the loading amount of MOF material (ie, CoNi-DABCO) in the MMMs obtained in this example was 30 wt.%.

[0063] Comparative Example 1

[0064] The difference from Example 1 is that, S3, a total of 1.8 g of PDMS is added to the dispersion obtained in S2 at one time, stirred evenly, 0.2 g of n-heptane is removed by volatilization, and then a crosslinking agent, ethyl orthosilicate, and a catalyst, dibutyltin dilaurate, are added, and mixed evenly to obtain a casting solution;

[0065] The rest of the steps are the same.

[0066] It was calculated that the loading amount of MOF material (ie, CoNi-DABCO) in the MMMs obtained in this comparative example was 10 wt.%.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that

[0069] S3, taking a total of 1.8g of PDMS and adding it to the dispersion obtained in S2, first adding 40wt.% of PDMS, stirring, then adding 30wt.%, 20wt.% and 10wt.% of PDMS in sequence, stirring evenly, volatilizing and removing 0.2g of n-heptane under stirring, then adding crosslinking agent ethyl orthosilicate and catalyst dibutyltin dilaurate, mixing evenly to obtain a casting solution;

[0070] The rest of the steps are the same.

[0071] It was calculated that the loading amount of MOF material (ie, CoNi-DABCO) in the MMMs obtained in this comparative example was 10 wt.%.

[0072] By comparing Example 1 and Control Example 1, it can be seen that if PDMS is added to the MOF dispersion at one time, the viscosity of the solution will increase rapidly, resulting in uneven mixing of MOF and PDMS, which in turn affects the performance of the product. Therefore, the present invention preferably adds PDMS to the MOF dispersion in multiple batches.

[0073] By comparing Example 1 and Control Example 2, it can be seen that if the amount of PDMS added in batches is improperly adjusted, uneven mixing between MOF particles and PDMS will result. PDMS has a large viscosity. In Example 1, a small amount of PDMS is first added, and then the amount of PDMS added is gradually increased, which is conducive to sufficient mixing between MOF and PDMS and improving the interface compatibility.

[0074] Comparative Example 1

[0075] 2 g of PDMS was added to 3 g of n-heptane, and after stirring for a period of time, a crosslinking agent, ethyl orthosilicate, and a catalyst, dibutyltin dilaurate, were added, and mixed evenly to obtain a casting solution;

[0076] The PVDF substrate pretreated with ethanol and deionized water was fixed on a glass plate with tape, and the casting liquid was cast on the PVDF substrate with a doctor blade. After the solvent was slowly evaporated at room temperature, the membrane was transferred to an oven at 80°C for drying to obtain a PDMS / PVDF membrane with a MOF material loading of 0 wt.%.

[0077] Comparative Example 2

[0078] The difference from Example 2 is that the process of preparing the MOF material CoNi-DABCO in S1 is not included, and the MOF material ZIF-71 of the same mass is directly selected in S2 to prepare MMMs.

[0079] The mixed matrix membranes provided in the embodiments, control examples and comparative examples were subjected to performance tests. Before the separation performance test, the membranes were activated under vacuum at 120° C. for 12 hours. The test conditions were: a mixed gas of CH4 / N2 (50:50, v / v) was set as the feed gas, the operating temperature was 25° C., and the feed pressure was 2 bar. The test results are shown in the following figure and Table 1:

[0080] in, Figure 5 The X-ray diffraction patterns of the CoNi-DABCO nanoparticles prepared in Example 1, the mixed matrix membranes provided in Examples 1-4 and Comparative Example 1 are shown in FIG. Figure 5 It can be seen that the characteristic peaks of the PDMS / PVDF of the comparative example and the intermediate CoNi-DABCO nanoparticles of Example 1 appear in the X-ray diffraction pattern of the MMMs provided in the example, indicating the successful combination of the CoNi-DABCO nanoparticles and the PDMS matrix, and the crystal structure of the MOF is not destroyed during the film preparation process.

[0081] Figure 6 The scanning electron microscope cross-sectional view of the CoNi-DABCO nanoparticles provided in the present application with a magnification of 6000 times and the MMMs provided in Comparative Example 1 and Examples 1-4 with a magnification of 1000 times; wherein, Figure 6 (a) is a scanning electron microscope cross-sectional image of CoNi-DABCO nanoparticles at a magnification of 6000 times. Figure 6 (b) is a scanning electron microscope cross-sectional view of the MMMs provided in Comparative Example 1 at a magnification of 1000 times, Figure 6 (c) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 1 at a magnification of 1000 times, Figure 6 (d) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 2 at a magnification of 1000 times, Figure 6 (e) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 3 at a magnification of 1000 times, Figure 6 (f) is a scanning electron microscope cross-sectional image of the MMMs provided in Example 4 at a magnification of 1000 times; Figure 7 The scanning electron microscope cross-sectional view of the CoNi-DABCO nanoparticles provided in the present application with a magnification of 6000 times and the MMMs provided in Comparative Example 1 and Examples 1-4 with a magnification of 5000 times; wherein, Figure 7 (a) is a scanning electron microscope cross-sectional image of CoNi-DABCO nanoparticles at a magnification of 6000 times. Figure 7 (b) is a scanning electron microscope cross-sectional view of the MMMs provided in Comparative Example 1 at a magnification of 5000 times, Figure 7(c) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 1 at a magnification of 5000 times, Figure 7 (d) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 2 at a magnification of 5000 times, Figure 7 (e) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 3 at a magnification of 5000 times, Figure 7 (f) is a scanning electron microscope cross-sectional image of the MMMs provided in Example 4 at a magnification of 5000 times; Figure 8 The scanning electron microscope surface image of the CoNi-DABCO nanoparticles provided in the present application with a magnification of 6000 times and the MMMs provided in Comparative Example 1 and Examples 1-4 with a magnification of 3000 times; wherein, Figure 8 (a) is a scanning electron microscope cross-sectional image of CoNi-DABCO nanoparticles at a magnification of 6000 times. Figure 8 (b) is a scanning electron microscope cross-sectional view of the MMMs provided in Comparative Example 1 at a magnification of 3000 times, Figure 8 (c) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 1 at a magnification of 3000 times, Figure 8 (d) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 2 at a magnification of 3000 times, Figure 8 (e) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 3 at a magnification of 3000 times, Figure 8 (f) is a scanning electron microscope cross-sectional view of the MMMs provided in Example 4 at a magnification of 5000 times; Figure 6-8 It can be seen from the cross-sectional view that the mixed matrix membrane prepared by the present invention has a dense structure, and the separation layer thickness is 22-27 μm; MOF particles are evenly dispersed in the PDMS matrix, and no obvious defects are observed when the MOF loading is increased to 30 wt.%, which is attributed to the good interfacial compatibility between PDMS and MOF. In contrast, MOF cannot be observed from the surface image of the membrane, indicating that MOF is well encapsulated in PDMS.

[0082] Fig. 9The comparison diagram of the experimental adsorption isotherm and theoretical adsorption isotherm of CH4 for MMMs at 298K provided in Example 2; PDMS is a rubbery polymer with relatively flexible molecular chains. When the pore size of the porous filler is larger than the size of the PDMS molecular chain, the filler pores will be blocked, which is not conducive to improving the gas permeation flux of MMMs. For example, in NaX@PDMS MMMs, when the NaX loading is 15%, 30% and 50%, respectively, the gas permeation flux decreases from about 3100 Barrer to 2070, 1860 and 890 Barrer (Polymer, 2004, 45, 5671-5681). In Mg2(dobdc)@PDMS MMMs, when the addition amount of Mg2(dobdc) is 20wt.%, the gas permeation flux decreases from 3100 Barrer to 2100 Barrer (Energy Environ. Sci., 2013, 6, 3565-3569). In the present invention, when the loading amount of CoNi-DABCO is 10wt.% and 20wt.%, the gas permeation flux of MMMs increases from 637 Barrer to 1072 and 1285 Barrer. The gas permeation flux of MMMs is much higher than that of PDMS / PVDF membrane, indicating that CoNi-DABCO does not have obvious pore clogging. The above conclusion is further verified by comparing the experimental gas adsorption amount and theoretical gas adsorption amount of MMMs. Fig. 9 It can be seen that the gas adsorption amount of the MMMs of 20wt.%-CoNi-DABCO provided in Example 2 is slightly lower than the theoretical value, indicating that the pores of CoNi-DABCO are not seriously blocked by PDMS molecular chains. Unlike NaX and Mg2(dobdc), the CoNi-DABCO used in the present invention has a smaller pore size, which makes it difficult for PDMS chains to enter the pores, alleviates the pore blockage, and achieves a significant increase in gas permeation flux.

[0083] Fig.10 The adsorption isotherms of CH4 and N2 for MMMs provided in Example 2 and Comparative Example 1 at 298K; Fig.10 It can be seen that compared with Comparative Example 1, the mixed matrix membrane loaded with 20 wt.% CoNi-DABCO provided in the present application has an adsorption capacity of CH4 increased by 5.5 times, and N2 increased by 2.2 times. The preferential adsorption of CH4 by CoNi-DABCO can make more CH4 molecules dissolve in the membrane, thereby promoting the transport of CH4 molecules in the membrane.

[0084] Fig.11 The CH4 / N2 separation performance comparison diagram of the MMMs provided in Example 2 and the reported separation membranes is shown in FIG. Fig.11It can be seen that most polymer membranes have low gas permeation flux and good selectivity, while MOF membranes have high gas permeation flux and moderate selectivity. The CoNi-DABCO@PDMS / PVDF MMMs prepared in the present invention exhibit high gas permeation flux and good selectivity, which is superior to the separation performance of most polymer membranes, MOF membranes and MMMs.

[0085] Fig.12 The structure diagram of ZIF-71 provided in Comparative Example 2 and CoNi-DABCO provided in Example 2, wherein Fig.12 The left picture is the structure diagram of ZIF-71, and the right picture is the structure diagram of CoNi-DABCO; Fig.12 Analysis shows that the structures and properties of ZIF-71 and CoNi-DABCO are very different, and their inherent structures and properties determine their application systems. 2+ and 4,5-dichloroimidazole to form a ZIF material with RHO topology, with a small window (0.48nm) and a large pore cage (1.68nm). ZIF-71 and most ZIF materials are hydrophobic (such as ZIF-8, ZIF-7, ZIF-90) and have strong affinity with organic solvent molecules, and are widely used in pervaporation. CoNi-DABCO is composed of Ni 2+ , potassium tetracyanonickelate hydrate and 1,4-diazaoctane to assemble a Hofmann-type MOF material. The Hofmann-type MOF material has a small pore size, a high density of unsaturated metal sites, and is adjacently distributed in a one-dimensional pore channel. This structure has a strong force on gas molecules. Therefore, in the separation of CH4 / N2, compared with the mixed matrix membrane loaded with 20wt.% ZIF-71 provided in Comparative Example 2, the mixed matrix membrane loaded with 20wt.% CoNi-DABCO provided in Example 2 exhibits better CH4 / N2 separation performance.

[0086] The CH4 / N2 separation performance parameter table of the MMMs provided in Comparative Example 1 and Examples 1-4 of the present invention is shown in Table 1 below:

[0087] Table 1 CH4 / N2 separation performance parameters of MMMs provided in Comparative Example 1 and Examples 1-4

[0088]

[0089] It can be seen from Table 1 that when the MOF loading is 20wt.%, the MMMs have the highest CH4 permeation flux. As the MOF loading further increases to 25wt.% and 30wt.%, the gas permeation flux decreases, which may be due to the agglomeration of MOF particles. Thanks to the good interfacial compatibility, the MMMs prepared in this application maintain good CH4 / N2 selectivity as a whole.

[0090] The CH4 / N2 separation performance parameter table of the MMMs provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is shown in Table 2 below:

[0091] Table 2 CH4 / N2 separation performance parameters of MMMs provided in Example 1, Comparative Example 1 and Comparative Example 2

[0092]

[0093] It can be seen from Table 2 that the MMMs provided by Control Examples 1 and 2 exhibit higher gas permeation flux and lower CH4 / N2 selectivity than Example 1. This is because adding PDMS to the MOF dispersion at one time or in an inappropriate ratio will lead to uneven mixing of MOF and PDMS, resulting in interface defects, resulting in increased gas permeation flux and reduced selectivity.

[0094] The CH4 / N2 separation performance parameter table of the MMMs provided in Comparative Example 1, Example 2 and Comparative Example 2 of the present invention is shown in Table 3 below:

[0095] Table 3 CH4 / N2 separation performance parameters of MMMs provided in Comparative Example 1, Example 2 and Comparative Example 2

[0096]

[0097] As shown in Table 3, compared with Example 2, the MMMs provided by Comparative Example 2 exhibited high gas permeation flux and low CH4 / N2 selectivity. This may be due to the high density of unsaturated metal sites in CoNi-DABCO enhancing the interaction with PDMS, and the good interface morphology ensures that the CH4 / N2 selectivity is not significantly reduced. When ZIF-71 is used as a filler, there are interface defects in the MMMs, and the gas permeation flux increases while the selectivity decreases.

[0098] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a MOF mixed matrix membrane for natural gas purification, characterized in that: The preparation method comprises the following steps: S1: dissolving a nickel source and a cobalt salt in deionized water, and then subjecting the mixture to ultrasonic treatment to obtain a suspension, dissolving 1,4-diazooctane in a methanol / water mixed solvent, and adding the mixture to the suspension, stirring the mixture at a certain temperature, and then centrifuging, washing, and drying the mixture to obtain CoNi-DABCO nanoparticles; S2: adding the CoNi-DABCO nanoparticles obtained in S1 into n-heptane, stirring and ultrasonicating to obtain a dispersion; S3: adding PDMS to the dispersion in S2 in batches, stirring, then adding a crosslinking agent and a catalyst, and mixing evenly to obtain a casting solution; the batch addition includes adding 5-10wt.%, 15-25wt.%, 25-35wt.% and 30-45wt.% of PDMS in sequence, and the total amount added is 100wt.%; S4: Fix the PVDF substrate on a glass plate, use a doctor blade to cast the casting solution obtained in S3 on the PVDF substrate, and after the solvent evaporates, perform drying to obtain the MOF mixed matrix membrane for natural gas purification.

2. The preparation method according to claim 1, characterized in that: The step S1 satisfies one or more of the following conditions: a. The nickel source comprises potassium tetracyanonic acid hydrate; b. The cobalt salt comprises cobalt nitrate hexahydrate; c. The ultrasonic treatment takes 0.5-1.0h; d. The stirring temperature is 40-45°C for 3-4h; e. The washing is carried out using methanol; f. The drying comprises drying in a vacuum oven at 120-150°C for 10-15h.

3. The preparation method according to claim 1 or 2, characterized in that: The step S1 also satisfies one or more of the following conditions: g. The molar ratio of the nickel source, the cobalt salt and 1,4-diazooctane is 1:1:1; h. The volume ratio of water to methanol in the mixed solvent is 1:

1.

4. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the CoNi-DABCO nanoparticles to the n-heptane is 1:5-15.

5. The preparation method according to claim 1, characterized in that: The step S3 satisfies one or more of the following conditions: i. The mass ratio of the amount of PDMS added to the CoNi-DABCO nanoparticles is 1:2-10; j. The crosslinking agent comprises tetraethyl orthosilicate; k. The catalyst includes dibutyltin dilaurate.

6. The preparation method according to claim 1, characterized in that: The step S4 satisfies one or more of the following conditions: l. The PVDF substrate was pretreated with ethanol and deionized water before the fixation; m. The drying temperature is 80-100°C.

7. The preparation method according to claim 1, characterized in that: Each time the PDMS is added, stirring is performed, and the total stirring time is 1-2 h.

8. A MOF mixed matrix membrane for natural gas purification, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Mixed matrix membrane of bead-like MOF filled silicone rubber

    CN112316741A

  • Preparation method of AC modified Cu-BTC-based mixed matrix membrane

    CN116785944A